Organizational justice, organizational learning and organizational image on engagement of young employees in commercial banks / Ibiwani Alisa Hussain - Hussain, Ibiwani Alisa (Institute of Graduate Studies, UiTM, 2015)
Young employees in organizations are becoming more demanding concerning justice and career development. The working culture of young employees is different compared to previous generations. Being different, this cohort brings in the “job hop” phenomena into the workforce and the attitude has observed reduction in level of engagement towards organizations. Engaged employees are important in organizations to enable them to acquire more knowledge and become multi skilled human capital through in-depth experience, with the assistance and support from mentor, coach and supervisor from the organizations. Scholars globally have been studied job satisfaction, job commitment, organizational citizenship behavior and the like among employees. However, there is still a dearth in studies to examine the relationship between employee engagement with organizational justice and organizational learning. This study examined the relationship between employee engagement with organizational justice and organizational learning, and the role of organizational image as mediator. The dependent variable was employee engagement, independent variables were organizational justice and organizational learning and organizational image was the mediating variable. For organizational justice, 3 dimensions were used in this study (1) distributive justice (2) procedural justice (3) interactional justice. Three dimensions were also used for organizational learning, (1) training (2) mentoring and (3) coaching…